Increasing self-care of patients with type-2 diabetes through implementation of nursing agency based on the health promotion model - Purwanto, Cucuk Rahmadi; Sukartini, Tintin; Bakar, Abu; Devy, Shrimarti Rukmini (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the effect of nursing agency model on fasting and 2-hour postprandial glucose levels in type 2 diabetics. Method: The quasi-experimental study was conducted from October to December 2021 in Lamongan, East Java, Indonesia, after approval from the ethics review committee of the University of Muhammadiyah, Lamongan, Indonesia. The sample comprised of type 2 diabetics of either gender aged 19-65 years who were able to move independently. The sample was divided into experimental group A, which was given nursing agency model training for six weeks, and control group B, which was only given diabetes treatment without any training. Patient self-care level was assessed using the Summary of Diabetes Self-Care Activities tool, while other variables were measured through fasting and 2-hour postprandial glucose levels. Data were analysed using a one-way covariance analysis test Results: Of the 256 individuals assessed, 42(16.4%) met the inclusion criteria, and, of them, 30(71.4%) comprised the final sample; 10(33.3%) males and 20(66.6%) females. Overall, 19(63.3%) patients were aged >50 years, and duration of diabetes was 5-10 years in 23(76.7%) cases. There were 15(50%) patients in each of the two groups. There was significant difference in the mean scores of all dimensions of self-care behaviour between the groups, and it increased significantly in group A post-intervention (p=0.05). There was a significant decrease in fasting and 2-hour postprandial glucose levels in group A compared to group B post-intervention (p=0.001). Conclusion: The application of the nursing agency model was found to be effective in increasing self-care ability and in reducing fasting and 2-hour postprandial blood glucose levels. Keywords: Blood glucose, Fasting, Diabetes mellitus, Self-care, Nursing.